Plasma galectin-3 is associated with decreased glomerular filtration rate in chronic HIV - Diana L. Vares-Lum; Louie Mar A. Gangcuangco; Juwon Park; Eduardo Manzano; Michael Ortega; Dominic C. Chow; Cecilia Shikuma (HIV Research & Clinical Practice)
Background People living with HIV (PLWH) have higher rates of chronic kidney disease (CKD) compared with HIV-uninfected individuals. The pathogenesis of CKD in HIV remains poorly understood but is likely from a combination of various factors, such as traditional comorbidities, prolonged antiretroviral therapy, immune dysregulation, and direct HIV effect on the kidneys. We evaluated plasma galectin-3 (Gal-3), a circulating marker of fibrosis, and its association with renal function. Methods Estimated glomerular filtration rate (eGFR) was assessed by CKD-EPI. Plasma galectin-3 was obtained from banked specimens by ELISA. Factors associated with eGFR were analyzed using step-wise multiple linear regression. Results A total of 45 PLWH and 58 HIV-uninfected participants were included with similar demographic parameters. Among PLWH, majority had undetectable plasma HIV RNA (82.2%). Gal-3 was significantly higher in PLWH than in HIV-uninfected participants (6.4 [IQR 4.0, 8.5] ng/mL and 4.5 [IQR 2.3, 6.5] ng/mL, respectively; p = 0.020) while a trend towards lower eGFR was found in PLWH compared to the HIV-uninfected cohort (86.8 [IQR 71.3, 91.8] and 89.0 [IQR 78.6, 97.4] mL/min/1.73 m2, respectively; p = 0.071). In univariable analysis, HIV status was marginally associated with decreased eGFR (β coefficient= −0.035, p = 0.051). In the final multivariable regression model adjusted for traditional risk factors of CKD, Gal-3 independently predicted a decrease in eGFR (unstandardized B= −0.008, p < 0.001) while HIV status did not demonstrate any significant association. Conclusion Gal-3 was higher in PLWH compared with HIV-uninfected participants. In multivariable adjusted analyses, Gal-3, but not HIV status, was associated with decreased eGFR. The role of Gal-3 as a biomarker of kidney function needs to be further elucidated.